Verb in the reading of Aban Bin Taghleb - ABBAS, Khadiga Majid AbdAl-HUSSAIN; Al-Abody, Hayder Muhammed Jabur (Al-Adab Journal, 2021)
The clause of the verb is what indicates the time and the event, and in the reading of Aban bin Tghlib in raising the verb indicated the case, such as his reading, Farad fought their condition is to fight, and among the accusative cases is the deletion of the noun from the verb and that is a request for mitigation, and the argument for his reading in the constructive is that he built the verb subject.